Addressing banks' vulnerability to deposit runs: Revisiting the facts, arguments and policy options - Thorsten Beck; Vasso Ioannidou; Enrico Perotti; Antonio Sánchez Serrano; Javier Suárez; Xavier Vives (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2024)
The recent banking turmoil was a stark reminder of the fragility associated with banks' funding structures, especially when they rely on an insufficiently diverse uninsured deposit base. Concerns about unrealised losses, triggered by the rapid shift in monetary policy, played a clear role in the run on Silicon Valley Bank. The forced merger of Credit Suisse with UBS showed what happens if a large bank's legacy and viability problems are left unresolved for a lengthy period. This may also crystalise in the need for sudden intervention by the authorities when investors' confidence breaks down, deposits are withdrawn on a massive scale and access to market funding is lost. The episodes of bank distress in the United States in March 2023 did not result in losses for uninsured deposits, signalling that these may effectively enjoy the same level of protection as explicitly insured deposits.This report of the Advisory Scientific Committee (ASC) of the European Systemic Risk Board (ESRB) reviews an extensive list of existing and potential policy tools that could be considered for addressing banks' vulnerability to runs and the underlying causes of this vulnerability.1 This report should not be misinterpreted as calling into question the benefits of the regulatory reform after the global financial crisis (i.e. Basel III). In the discussion, we pay specific attention to (i) how each option affects the allocation of potential losses across agents, (ii) the implications of each option for risk-taking, (iii) the effectiveness of each option in reducing bank funding fragility, and (iv) the likely impact of each option on the cost of intermediation. We are aware that even the options considered to have the greatest merit would need further careful technical assessment and refinement before being adopted. We order the policy options into two lists of categories. The first includes options that could be further considered without major structural changes to the current regulatory and supervisory framework, and which might be implemented in the form of adjustments within the margins of discretion of Basel III.
Keywords: 330; bank; bank deposit; financial stability; fund (EU); interest; monetary policy; report